CONCEPT OF MANAGEMENT EDUCATION ACCREDITATION - Andrey N. Pyshkin (Высшее образование в России)
The article proposes conceptual approaches to the independent accreditation of academic programs in management. These approaches are based on the analyses of some project within Federal Education Development Program and author's participation experience in a couple of them. Developed with the Ministry's support in 2011-2015 independent accreditation and monitoring models are not widespread, the new assessment organizations didn't appear, and independent accreditation tools are almost equal to those that are used in the procedures of the state accreditation. The concept proposes alternative approaches to the structure, procedure and the content of the independent accreditation that can be used in the framework of the Federal Support Policy and for development of independent accreditation system for leading programs in management.